The complete chloroplast genome sequence of three medicinal species; Curcuma longa, Curcuma wenyujin, and Curcuma phaeocaulis (Zingiberaceae) - Kim, Min-Kyeoung (Mitochondrial DNA B Resour, 2021)
Curcuma longa, C. wenyujin and C. phaeocaulis are important herbal medicine which of rhizomatous herbaceous perennial plant of the family Zingiberaceae. This study generated a complete chloroplast genome sequence of three medicinal species were characterized by de novo assembly with whole genome sequencing data. The length of complete chloroplast genome were 162,180 bp (C. longa), 162,266 bp (C. wenyujin), and 162,133 bp (C. phaeocaulis), respectively, with four structures that were included in large single copy region (87,001 bp, 87,042 bp, and 87,013 bp), small single copy region (15,681 bp, 15,710 bp, and 15,622 bp), and duplicated inverted regions (29,749 bp, 29,757 bp and 29,749 bp of each). Based on phylogenetic trees, C. longa, C. wenyujin, and C. phaeocaulis were grouped by high bootstrap value with Curcuma species. This result approved that C. longa, C. wenyujin and C. phaeocaulis were comprised in Alpinia and Wurfbainia. Therefore, this chloroplast genome data firstly generated valuable genetic resource in discrimination of herbal materials, phylogeny and development DNA marker.